The Conserving Agrarian Land for Future Generations: A Policy Blueprint for Indonesia - Anis Mashdurohatun; Muslimah Hayati; Saritua Silitonga; Zaenal Arifin; Amanda Amanda (Unissula, 2025)
This study examines the current laws and regulations on land conversion that have not been able to uphold ecological justice, challenges in the prevailing laws and regulations; and the reconstruction of these laws and regulations to comply with the values of ecological justice. This research aims to improve the protection of sustainable food agricultural land for future generations. This study used a normative legal method. The results of the study indicate that the Indonesian regulatory framework has not been able to achieve ecological justice due to competing demands between agrarian and non-agricultural land use. The government's regulatory authority derived from the 1945 Constitution often prioritizes economic goals over ecological justice, so that land protection policies are inadequate. This study concludes with a proposal to reconstruct the regulatory framework to comply with the principle of ecological justice, by proposing specific changes to Articles 2, 23, 39, 42, and 70 of Law No. 41 of 2009, Article 103 of PP No. 26 of 2021, and Article 44 of Law No. 41 of 2009 as amended by the Job Creation Law No. 6 of 2023. This study recommends integrating ecological justice into the legal framework, enhancing provisions to mandate local government participation, and strengthening governance and law enforcement in conserving agrarian land.